Histopathological and immunohistochemical characterization of a mixed tubule papillary thyroid carcinoma in a Nellore cow - Braga, Iolanda Simões [UNESP]; Ximenes, Pedro Pol [UNESP]; Dinau, Fernando Carmona [UNESP]; de Moura, Fernanda Barthelson Carvalho [UNESP]; Contel, Isabeli Joaquim [UNESP]; de Souza, Giovanna Gati [UNESP]; Pelaquim, Isadora Fernanda [UNESP]; Rocha, Noeme Sousa [UNESP] (Brazilian Journal of Veterinary Pathology, 2024)
Reports on thyroid carcinomas in bovines are scarce. An 18-year-old Nellore cow was referred to a veterinary hospital due to lateral recumbency lasting one day after falling on irregular terrain. The patient was clinically diagnosed with spinal cord injury. Necropsy and histopathology revealed a thyroid tubule papillary carcinoma. Immunohistochemical analysis revealed discrete positive cells for calcitonin, moderately positive cells for thyroid transcription factor 1 (TTF-1), and strongly positive cells for thyroglobulin in the thyroid gland. Thus, this report describes a case of a mixed tubule papillary carcinoma derived from both medullary and follicular cells in a Nellore cow.
Keywords: bovine; histopathology; immunohistochemistry; thyroid carcinoma